Gas-LiquidMassTransferin Continuous Oscillatory Flow BaaledColumnina - Taslim Taslim; Mahd. Sabri Takriff (Department of Chemical Engineering, Universitas Gadjah Mada, 2004)
Gas-liquid mass transfer in continuous oscillatory flow was conducted in a vertical baffled column. Pure carbon dioxide (C02) was used as the dispersed phase and tap water was used as the continuous phase. The mass transfer rate of C02 measured under continuous operation was expressed in terms of the liquid-side volumetric mass transfer coefficient (kLa) and was calculated using a stationary method. The effects of oscillation frequency, oscillation amplitude, and flow rates on mass transfer were also determined. The results showed that a significant increase in mass transfer could be achieved in oscillatory flow in a baffled column comp.:lfed to that in a bubble column. The mass transfer in continuous oscillatory flow in a baffled column was not affected by the liquid flow rate in the range tested. Then, kLQwas correlated as a function of power density and superficial gas velocity.